2016
DOI: 10.7150/ijms.16571
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of lncRNA H19/miR-675 promotes tumorigenesis in head and neck squamous cell carcinoma

Abstract: There is accumulating evidence indicating that long non-coding RNA H19 and its mature product miR-675 play essential roles for tumor growth and progression. However, their prognostic value in human head and neck squamous cell carcinoma (HNSCC), particular in laryngeal carcinoma, remains to be elucidated. In this study, we observed that both H19 and miR-675 were significantly overexpressed in a cohort of 65 primary tumor samples and two HNSCC cell lines. Importantly, when paired with patient follow-up data, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 31 publications
0
55
0
Order By: Relevance
“…Recent studies have found that long non‐coding RNAs (LncRNAs), a member of non‐coding RNA gene family, are dysregulated in laryngeal cancer tissues . More interestingly, several LncRNAs, such as HOTAIR, NEAT1 and H19, function as oncogenes to promote the tumorigenesis of laryngeal cancer. Therefore, identifying the role of LncRNAs in laryngeal cancer may bring a novel insight into the occurrence and development of laryngeal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that long non‐coding RNAs (LncRNAs), a member of non‐coding RNA gene family, are dysregulated in laryngeal cancer tissues . More interestingly, several LncRNAs, such as HOTAIR, NEAT1 and H19, function as oncogenes to promote the tumorigenesis of laryngeal cancer. Therefore, identifying the role of LncRNAs in laryngeal cancer may bring a novel insight into the occurrence and development of laryngeal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…H19 is first reported to be overexpressed in bladder carcinoma and has been indicated as a predict marker in cancer (Fellig et al, ). Overexpression of H19 can induce HNSCC progression (Guan et al, ). H19 is reported to be increased in glioma tissue and suggests poor patient survival (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have demonstrated that lncRNAs are associated with the occurrence and development of a variety of cancers . Several lncRNAs, such as UCA1, H19, and PVT1, have been reported in human head and neck carcinoma . To identify the biological function of KCNQ1OT1 in MSSCC, we demonstrated KCNQ1OT1 was upregulated in MSSCC tissues and the IMC‐3 cell line for the first time.…”
Section: Discussionmentioning
confidence: 83%
“…[26][27][28] Several lncRNAs, such as UCA1, H19, and PVT1, have been reported in human head and neck carcinoma. [29][30][31] To identify the biological function of KCNQ1OT1 in MSSCC, we demonstrated KCNQ1OT1 was upregulated in MSSCC tissues and the IMC-3 cell line for the first time. By performing loss-of-function experiments, we discovered KCNQ1OT1 promoted cell proliferation, migration, and invasion in MSSCC.…”
Section: Discussionmentioning
confidence: 99%